2008
DOI: 10.1002/pd.1898
|View full text |Cite
|
Sign up to set email alerts
|

Use of the combined first‐trimester screen result and low PAPP‐A to predict risk of adverse fetal outcomes

Abstract: ObjectivesTo investigate associations between combined first‐trimester screen result, pregnancy associated plasma protein‐A (PAPP‐A) level and adverse fetal outcomes in women.MethodsPregnancy outcomes for 10 273 women participating in a community based first‐trimester screening (FTS) programme in Western Australia were ascertained by record linkage to birth and birth defect databases. A first‐trimester risk cut‐off of ≥ 1 in 300 defined screen positive women.ResultsScreen positive pregnancies were more likely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
63
1
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(77 citation statements)
references
References 30 publications
9
63
1
2
Order By: Relevance
“…1 As obtained by logistic regression equations including terms for SGA (n = 2,134) or FGR (n = 1,975) as outcome variables and PAPP-A, ␤-hCG, BMI <10th percentile and smoking at enrolment as dichotomous categorical variables. From a biologic point of view, PAPP-A plays a significant etiologic role in promoting fetal growth by breaking down IGF-binding proteins [6]. Given the heterogeneity of etiologic factors associated with FGR and the role of other proteins and hormones regulating fetal growth [6][7][8][9][10][11][12][13][14][15][16][17][18][19], it is likely that the activity of PAPP-A, although important, is only one of a number of factors regulating fetal growth processes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 As obtained by logistic regression equations including terms for SGA (n = 2,134) or FGR (n = 1,975) as outcome variables and PAPP-A, ␤-hCG, BMI <10th percentile and smoking at enrolment as dichotomous categorical variables. From a biologic point of view, PAPP-A plays a significant etiologic role in promoting fetal growth by breaking down IGF-binding proteins [6]. Given the heterogeneity of etiologic factors associated with FGR and the role of other proteins and hormones regulating fetal growth [6][7][8][9][10][11][12][13][14][15][16][17][18][19], it is likely that the activity of PAPP-A, although important, is only one of a number of factors regulating fetal growth processes.…”
Section: Discussionmentioning
confidence: 99%
“…Literature data suggest that first-trimester maternal serum concentrations of PAPP-A below the 10th percentile are associated with an OR of SGA between 2 and 5 [3][4][5][6]. Given our sample of 2,000, women our study had 90.2% power (␣ !…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have demonstrated an association between decreased first trimester PAPP-A concentrations and intrauterine growth restriction, 4-7 low birthweight, 7-10 preterm delivery, [4][5][6][9][10][11] stillbirth after 24 weeks gestation, 9,10,12 increased risk of miscarriage, pregnancy-induced hypertension and gestational diabetes. 4,5,9 Previous studies have also identified adverse obstetric outcomes associated with single markers such as increased fetal NT 13,14 and abnormal free β-hCG levels, 15 and among pregnancies identified at increased risk of Down syndrome, there was a greater risk of poor outcomes such as spontaneous abortion, placenta praevia, intrauterine fetal demise, pregnancy-induced hypertension and preterm labour.…”
Section: Introductionmentioning
confidence: 98%
“…First trimester screening done in our Case 2 showed low PAPP-A. However, this finding is non-specific and has been associated with a number of conditions and adverse fetal outcomes including preterm birth, preeclampsia, low birth weight and pregnancy loss (Dugoff et al, 2004;Barrett et al, 2008). The cystic hygroma detected in our first case has been associated with a variety of conditions including aneuploidy, pregnancy loss and genetic syndromes such as Noonan syndrome (Malone et al, 2005).…”
Section: Discussionmentioning
confidence: 92%